Tinjauan fiqih mu’amalah pada praktik pengambilan ujroh bagi calo sewa menyewa mobil di Pontianak - Khairunnisa, Dina; Dimas Satria, Wahyu (Asy-Syari’ah : Jurnal Hukum Islam, 2024)
Car rental brokers in Pontianak are the people's choice in car rental, with the difference in prices taken from car rental, this research aims to describe and analyze the practice of brokering in car rental in Pontianak and find out the profit-making practices of car rental brokers in Pontianak. according to the Muamalah Fiqh review. Researchers used a qualitative research method with an empirical juridical approach, with primary data obtained from interviews with brokers, rental owners and car rental consumers in Pontianak. As for secondary data obtained from classical books, journals and sources from the internet that are relevant to the focus of research. Data collection techniques were obtained through observation, interviews and documentation. The results showed that the practice of brokering between rental owners and brokers in the agreement contract carried out by verbal agreement is in accordance with article 1320 of the Civil Code, KHES Book II Articles 487-500 and Fiqh Muamalah regarding wakalah. The practice of taking advantage of brokers from the difference in prices from rental packages, increasing prices during major events, increasing prices above market prices due to the needs of brokers' lives is reasonable and permissible as long as it does not cheat and violate the agreement in accordance with the provisions of Fiqh Muamalah.